1998
DOI: 10.1093/bja/81.5.707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of i.v. ketamine in combination with epidural bupivacaine or epidural morphine on postoperative pain and wound tenderness after renal surgery

Abstract: We studied 60 patients undergoing operation on the kidney with combined general and epidural anaesthesia, in a double-blind, randomized, controlled study. Patients were allocated to receive a preoperative bolus dose of ketamine 10 mg i.v., followed by an i.v. infusion of ketamine 10 mg h-1 for 48 h after operation, or placebo. During the first 24 h after surgery, all patients received 4 ml h-1 of epidural bupivacaine 2.5 mg ml-1. From 24 to 48 h after operation, patients received epidural morphine 0.2 mg h-1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 34 publications
3
39
0
1
Order By: Relevance
“…In upper abdominal surgery, therefore, multiple blockades of afferent nociception may be necessary to attain definitive preemptive analgesia. Although previous studies have shown that preemptive application of low-dose IV ketamine reduces postoperative pain and the consumption of opioids [8,10], we were not able to find any study examining the effect of the combination we used (ropivacaine + ketamine).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In upper abdominal surgery, therefore, multiple blockades of afferent nociception may be necessary to attain definitive preemptive analgesia. Although previous studies have shown that preemptive application of low-dose IV ketamine reduces postoperative pain and the consumption of opioids [8,10], we were not able to find any study examining the effect of the combination we used (ropivacaine + ketamine).…”
Section: Discussionmentioning
confidence: 89%
“…The visceroperitoneal organs are innervated multiply by the spinal nerves T5-T12 [13], the vagus nerve [5,6,14], and the phrenic nerve (C3-C5) [8,13] in the upper abdomen. All of these nerves are closely associated with visceroperitoneal nociception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cochrane review of ketamine for postoperative pain reported in 27 of 37 reviewed trials ketamine reduced opioid analgesic requirements or pain intensity, or both [14]. Four of these trials included a preincisional bolus of ketamine (10 mg, 0.15 mg/kg, ) for 24 postoperative hours [2,[14][15][16][17][18]. The four trials included major abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Santral sensitizasyon ketamin ve dekstrometorfan gibi NMDA reseptör antagonistleri yanında, hücre içine kalsiyum girişini engelleyen verapamil gibi kalsiyum kanal blokerleri ile de önlenebilir. Nitekim klinikte kullanılabilen bir NMDA antagonisti olan ketaminin postoperatif ağrıyı ve postoperatif hasta kontrollü morfin tüketimini (HKA) azalttığını göste-ren klinik çalışmalar bulunmaktadır (10)(11)(12)(13)(14)(15). Kalsiyum kanal blokerlerinin de hayvan deneylerinde antinosiseptif etki sağladığı, kronik ağrısı olan vakalarda morfin analjezisini potansiyalize ettiği ve akut postoperatif ağrıda hasta kontrollü analjezi ile opioid tüketimini azalttığını gösteren çalışmalar mevcuttur (4,5,(16)(17)(18).…”
unclassified